Archaeological records of Megalobulimus shells as artifacts in South America - Gordillo, Sandra (2019)
The remains of Megalobulimus shells in archaeological contexts have been recorded in Argentina, Brazil, Chile, Ecuador, Paraguay, Perú, Uruguay and Venezuela.This signifies that Megalobulimus shells was an important asset of high value and used in trade and exchange networks. The predominant type of artifact recovered is perforated beads, however, whole Megalobulimus shells were also used as functional containers of substances, or as symbolic objects.